Future Wars - Dupuy, Trevor (London Sidgwick & Jackson, 1992)
The author is an American military historian who has produced an analysis of where a number of large-scale conventional wars might happen, how they would be fought and who will win. The book is a product of the strategic forecasting group that foresaw the course and outcome of the Gulf War.
Includes Appendices and Glossary
Keywords: War -- Forecasting -- Limited War